Crafts in the Contemporary Creative Economy - Martha Friel (Aisthesis, 2020)
Speaking generically of crafts from an economic point of view means referring to a field that encompasses different sectors and professions, an agglomeration of very different activities in terms of economic structure, performance and needs. This paper, however, aims to analyse only some of the artisan worlds, i.e. traditional trades, art & crafts which, even if manifesting themselves today in new ways, interest us more than others because of the genius loci they have subsumed. This is because this is the main feature that allows us to count on their survival in a present and in a future in which even large industries are looking with great interest at limited and customized production, and where not only major companies but also local and regional entities are rediscovering activities closely related to the “sense of place”, such as crafts, and including them in their identity branding policies. After an introductory look at the role of craftsmanship today in the “creative economy”, the paper describes the problems facing this productive and cultural sector today and outlines the challenges for the near future.